Risk and accountability: Drivers for change in network governance. The case of school restaurants governance in a Swiss city - Nathalie Brender; Bledi Yzeiraj; Florian Dupuy (Cogent Business & Management, 2017)
Growing requirements for accountability and risk management put decentralized models of public governance under pressure. This article investigates the drivers for change from a completely decentralized, network-oriented model to a more centralized, and procedural governance model of school restaurants in a Swiss city. It focuses on the pressures and challenges that this municipality faces in terms of risks and accountability in order to identify the conditions in which network governance can be successful. We applied a qualitative approach that combined conducting 25 semi-structured interviews of main stakeholders and analyzing documentation. We found that increased demand for school meals from families, the perception of increasing exposure to insufficiently managed risks associated with growing accountability requirements constitute the main drivers for change to the centralization of certain risk-sensitive, costly, and low social purpose activities, thus providing the municipality authorities with more control over the system while preserving the associative function.
Keywords: 650